Comparison of [18F]FDG PET/CT with magnetic resonance imaging for the assessment of human brown adipose tissue activity - Jonas Gabriel William Fischer; Claudia Irene Maushart; Anton S. Becker; Julian Müller; Philipp Madoerin; Alin Chirindel; Damian Wild; Edwin E. G. W. ter Voert; Oliver Bieri; Irene Burger; Matthias Johannes Betz (EJNMMI Research, 2020)
Abstract Background Brown adipose tissue (BAT) is a thermogenic tissue which can generate heat in response to mild cold exposure. As it constitutes a promising target in the fight against obesity, we need reliable techniques to quantify its activity in response to therapeutic interventions. The current standard for the quantification of BAT activity is [18F]FDG PET/CT. Various sequences in magnetic resonance imaging (MRI), including those measuring its relative fat content (fat fraction), have been proposed and evaluated in small proof-of-principle studies, showing diverging results. Here, we systematically compare the predictive value of adipose tissue fat fraction measured by MRI to the results of [18F]FDG PET/CT. Methods We analyzed the diagnostic reliability of MRI measured fat fraction (FF) for the estimation of human BAT activity in two cohorts of healthy volunteers participating in two prospective clinical trials (NCT03189511, NCT03269747). In both cohorts, BAT activity was stimulated by mild cold exposure. In cohort 1, we performed [18F]FDG PET/MRI; in cohort 2, we used [18F]FDG PET/CT followed by MRI. Fat fraction was determined by 2-point Dixon and 6-point Dixon measurement, respectively. Fat fraction values were compared to SUVmean in the corresponding tissue depot by simple linear regression. Results In total, 33 male participants with a mean age of 23.9 years and a mean BMI of 22.8 kg/m2 were recruited. In 32 participants, active BAT was visible. On an intra-individual level, FF was significantly lower in high-SUV areas compared to low-SUV areas (cohort 1: p < 0.0001 and cohort 2: p = 0.0002). The FF of the supraclavicular adipose tissue depot was inversely related to its metabolic activity (SUVmean) in both cohorts (cohort 1: R 2 = 0.18, p = 0.09 and cohort 2: R 2 = 0.42, p = 0.009). Conclusion MRI FF explains only about 40% of the variation in BAT glucose uptake. Thus, it can currently not be used to substitute [18F] FDG PET-based imaging for quantification of BAT activity. Trial registration ClinicalTrials.gov. NCT03189511 , registered on June 17, 2017, actual study start date was on May 31, 2017, retrospectively registered. NCT03269747 , registered on September 01, 2017.